Fan foundation concrete and preparation method thereof
By using specific group distribution ratios in fan foundation concrete, including modified fibers, slag powder, waste tiles sand and fly ash, the problems of decreased strength and durability of fan foundation concrete in wind-drying and sun-drying environments are solved, and higher impact, earthquake and wear resistance are achieved, and the service life of concrete is extended.
Patent Information
- Application Number
- CN202510041943.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-05-02
AI Technical Summary
Fan foundation concrete has problems of decreased strength and durability in long-term wind-drying and sun-drying environments.
A fan-based concrete formula is adopted, including cement, river sand, gravel, water, modified fiber, slag powder, waste ceramic tiles, polycarboxylic acid water reducer and fly ash. Through the combination of these components, the strength, crack resistance and durability of the concrete are improved.
It significantly improves the impact resistance, earthquake resistance, and anti-shock resistance of concrete, enhances the anti-seepage and frost resistance, and extends the service life of concrete.
Smart Images

Figure BDA0005237214200000091 
Figure BDA0005237214200000101
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of concrete, and in particular to a wind turbine foundation concrete and a preparation method thereof. Background Art
[0002] Wind turbine foundation concrete is a vital component in wind farm construction. As the basic supporting structure of the wind turbine, wind turbine foundation concrete needs to withstand the weight of the wind turbine, wind force and other environmental factors. Its quality and stability are directly related to the operation effect and life of the wind turbine.
[0003] Wind turbine foundation concrete is usually composed of cement, sand, gravel, water reducer, filler, fiber, water and admixtures. After cement and water are mixed, cement gelation reaction occurs to generate hardened cement glue, which fills the voids in the concrete, increases the density of the concrete, and thus increases the strength of the concrete. Sand and gravel are piled into a tight framework in the concrete, acting as a skeleton, making the concrete more stable and durable. Fiber can hinder the generation and development of micro cracks in concrete and improve the crack resistance of concrete. The concrete prepared by mixing various components has excellent comprehensive performance.
[0004] However, wind turbine foundation concrete needs to adapt to different geological and climatic conditions, and needs to withstand the huge load generated by wind turbines while having good durability. Generally, concrete will experience problems such as decreased strength and durability under long-term wind and sun exposure. Summary of the invention
[0005] In order to improve the problem of reduced strength and durability of concrete in a long-term wind and sun environment, the present application provides a wind turbine foundation concrete and a preparation method thereof.
[0006] The present application provides a wind turbine foundation concrete, which adopts the following technical solution: A wind turbine foundation concrete comprises the following raw materials, measured by weight: 200-220 parts of cement, 40-45 parts of river sand, 33-36 parts of crushed stone, 120-160 parts of water, 22-25 parts of modified fiber, 30-35 parts of slag powder, 18-20 parts of waste tile sand, 10-15 parts of polycarboxylic acid water reducer and 25-30 parts of fly ash.
[0007] By adopting the above technical solution, cement plays the role of a cementitious material in concrete, which can bond river sand, crushed stone and other coarse aggregates together, solidify and generate strength. Cement and water form cement slurry, which wraps around the surface of coarse and fine aggregates and fills the gaps between aggregates. River sand, as a fine aggregate, plays the role of filling the gaps between coarse aggregates, increasing the density of concrete, and improving strength and durability. The filling gaps between crushed stones can effectively improve the density of concrete, enhance the internal connectivity of concrete, and thus improve the strength and durability of concrete. When concrete is impacted, the modified fiber can absorb a large amount of energy, effectively reduce the effect of concentrated stress, prevent the development of concrete cracks, and can enhance the impact resistance, earthquake resistance, and anti-scouring and wear resistance of concrete. At the same time, it improves the impermeability, which is conducive to the improvement of anti-freeze ability.
[0008] Slag powder effectively inhibits the alkali-aggregate reaction of concrete, improves its resistance to seawater erosion, and can also reduce the hydration heat of concrete and reduce the risk of cracking. Waste tile sand is used as concrete aggregate. Its large porosity makes concrete have good thermal insulation properties, increases the water consumption of the standard consistency of the net paste, shortens the initial setting time, is conducive to the hydration of cement, and increases the hydration rate. Polycarboxylic acid water reducer can be adsorbed on the surface of cement particles to form a layer of charge, produce an electrostatic repulsion effect, increase the distance between cement particles, reduce flocculation, and thus improve the fluidity of concrete. Fly ash improves the workability of concrete and inhibits water seepage. The active ingredients in fly ash react with cement hydration products to improve the later strength of concrete. Various components play an important role in the wind turbine foundation concrete, and together constitute a high-performance and high-durability concrete structure to ensure the quality and durability of concrete.
[0009] Preferably, the method for preparing the modified fiber comprises the following steps: (1) dispersing silk in a sodium hydroxide solution to obtain a silk protein solution, washing, drying, extruding granulation, and melt spinning to obtain silk fibers; (2) dispersing the modified bamboo scraps in deionized water, adding the silk fibers from step (1), stirring at a temperature of 80-85° C. for 1-2 h, and drying to obtain a mixture; (3) spraying a water-soluble epoxy resin adhesive onto the surface of the mixture in step (2), and drying to obtain modified fibers.
[0010] By adopting the above technical scheme, silk is dispersed in a sodium hydroxide solution to destroy certain chemical bonds or structures in the silk, the silk is dispersed to obtain a silk protein liquid, the residual sodium hydroxide and other possible impurities in the silk protein liquid are removed by washing, extrusion granulation is performed, and melt spinning is performed to obtain silk fibers with high tensile strength, impact resistance, and crack resistance.
[0011] The modified bamboo chips have good toughness, adsorption and bending resistance, and can be loaded on the surface of silk fibers to improve the strength, toughness, biocompatibility and adsorption of silk fibers. Water-soluble epoxy resin adhesive is sprayed on the surface of the mixture. The water-soluble epoxy resin adhesive has excellent bonding properties, wear resistance and corrosion resistance, so that the modified bamboo chips adhere to the surface of silk fibers. At the same time, the combination of modified bamboo chips and silk fibers increases the toughness, durability and mechanical strength of silk fibers. It is subsequently used in wind turbine foundation concrete to increase the strength, crack resistance and durability of the concrete.
[0012] Preferably, the mass ratio of the silk fiber, the modified bamboo chips and the water-soluble epoxy resin adhesive is 1:0.3-0.5:0.07-0.09.
[0013] By adopting the above technical scheme, the mass ratio of silk fiber, modified bamboo chips and water-soluble epoxy resin adhesive is further limited within a certain range, and the obtained modified fiber has excellent mechanical properties, crack resistance and wear resistance. Silk fiber has the characteristics of high strength, high toughness, good wear resistance and corrosion resistance, and the modified bamboo chips have good adsorption, toughness and crack resistance. The modified bamboo chips can be loaded on the surface of silk fiber to improve the mechanical properties of silk fiber. The water-soluble epoxy resin adhesive has excellent bonding performance, wear resistance and corrosion resistance, so that the modified bamboo chips can be stably adhered to the surface of silk fiber, increasing the waterproofness and durability of silk fiber. It is subsequently applied to concrete to improve the compressive, tensile and shear strength of concrete, and also improve the crack resistance, waterproofness and corrosion resistance of concrete, extending the service life of concrete.
[0014] Preferably, the preparation method of the modified bamboo chips comprises the following steps: dispersing the wood chips in a potassium hydroxide solution, soaking for 1-2 hours, washing with water, and then dispersing them in deionized water, adding marble powder, sodium lignin sulfonate and xanthan gum, stirring at a temperature of 75-80°C for 1-2 hours, drying, and grinding to obtain modified bamboo chips.
[0015] By adopting the above technical solution, potassium hydroxide is used to activate the sawdust, remove some impurities in the sawdust, increase the specific surface area of the sawdust, and increase the active sites on its surface to prepare for subsequent reactions. Marble powder has good strength and durability, fine particle size and large surface area, and can be loaded on the surface and pores of the sawdust to improve the strength and durability of the sawdust. Sodium lignin sulfonate has a strong dispersing ability and can effectively disperse the sawdust and marble powder in deionized water.
[0016] Xanthan gum has a certain viscosity, which makes the marble powder adhere to the surface and pores of the sawdust, improving the strength, viscosity and stability of the sawdust. In addition, xanthan gum also has good suspension and dispersion properties, which helps to maintain the uniform distribution of sawdust and marble powder in the system. The mixture of sawdust, marble powder, sodium lignin sulfonate and xanthan gum further increases the strength, wear resistance and adhesion of the modified sawdust, which is subsequently applied to silk fibers to improve the coordination of the various components in the silk fibers, thereby subsequently improving the corresponding performance of concrete.
[0017] Preferably, the mass ratio of the sawdust, marble powder and xanthan gum is 1:0.6-0.8:0.1-0.2.
[0018] By adopting the above technical scheme, the mass ratio of sawdust, marble powder and xanthan gum is further limited within a certain range, and the modified sawdust obtained has good comprehensive performance. Sawdust has good toughness and adsorption, marble powder has good hardness and wear resistance, marble powder can be loaded on the surface and pores of sawdust, improve the strength and durability of sawdust, and xanthan gum has good viscosity and fluidity, so that marble powder adheres to the surface of sawdust, improves the mechanical properties of sawdust, sawdust, marble powder and xanthan gum. Subsequent application in concrete, sawdust, marble powder and xanthan gum have synergistic effect, improve the working performance and durability of concrete.
[0019] Preferably, the method for preparing waste tile sand comprises the following steps: (1) crushing the waste tile sand to a particle size of less than 2 mm, then dispersing it in a sodium hydroxide solution, soaking it at 75-80° C. for 1-2 hours, washing it with water, and then dispersing it in dilute hydrochloric acid, soaking it at room temperature for 1-2 hours, washing it with water, filtering it, and drying it to obtain pretreated waste tile sand; (2) Dispersing the modified starch in deionized water, stirring evenly, adding the pretreated waste tile sand in step (1), continuing to stir, then adding silicon carbide whiskers and erythritol, stirring at a temperature of 60-65° C. for 2-3 hours, drying, and crushing to obtain waste tile sand.
[0020] By adopting the above technical scheme, sodium hydroxide effectively reacts with certain components (such as silicates, etc.) in the waste tile sand to remove impurities, and dilute hydrochloric acid reacts with other components in the waste tile sand to further purify the waste tile sand.
[0021] Modified starch is dispersed in deionized water, and waste tile sand is added. The waste tile sand is evenly distributed in the starch solution. Silicon carbide whiskers have high strength and toughness and can adhere to the surface and pores of the waste tile sand, increasing the strength and specific surface area of the waste tile sand. Erythritol has good dispersibility, so the waste tile sand, modified starch and erythritol are mixed evenly. The obtained waste tile sand has good strength, toughness and wear resistance, and is subsequently used in concrete to improve the performance of concrete, enhance the strength of concrete, and improve the toughness and wear resistance of concrete.
[0022] Preferably, the mass ratio of the waste tile sand, modified starch and silicon carbide whisker is 1:0.6-0.8:0.1-0.3.
[0023] By adopting the above technical scheme, the mass ratio of waste tile sand, modified starch and silicon carbide whiskers is further limited within a certain range, and the obtained waste tile sand has better comprehensive performance. The waste tile sand has more pores, and the silicon carbide whiskers have very high strength and modulus, and can be loaded on the surface and pores of the waste tile sand, thereby improving the tensile strength, flexural strength, toughness and wear resistance of the waste tile sand. The modified starch has a certain viscosity, so that the waste tile sand and silicon carbide whiskers adhere closely, thereby increasing the strength and durability of the waste tile sand. In the subsequent application in concrete, the waste tile sand, modified starch and silicon carbide whiskers work together to make the concrete have better crack resistance and deformation resistance when facing external forces, thereby extending the service life of the concrete.
[0024] Preferably, the preparation method of the modified starch comprises the following steps: dispersing corn starch in deionized water, stirring at a temperature of 76-80°C for 30-35 minutes, adding hydrochloric acid and a silane coupling agent, stirring for 1-2 hours, and drying to obtain pretreated starch, dispersing the pretreated starch in deionized water, adding nano-silicon dioxide and carboxymethyl cellulose, stirring at a temperature of 60-65°C for 1-2 hours, drying, and grinding to obtain modified starch.
[0025] By adopting the above technical scheme, hydrochloric acid can accelerate the breaking of glycosidic bonds in starch molecules, so that they are hydrolyzed into simple sugar molecules such as polysaccharides, oligosaccharides, maltose, glucose, etc. The silane coupling agent reacts with the hydroxyl groups of the starch molecules to form silicon-oxygen bonds and ether bonds, thereby modifying the surface of the starch, enhancing the interaction between the starch particles and the polymer, improving the heat resistance and water resistance of the starch, and enhancing the compatibility with other materials.
[0026] Pretreated starch is dispersed in deionized water, and nano-silicon dioxide and carboxymethyl cellulose are added. Nano-silicon dioxide has high mechanical strength, wear resistance and heat resistance, and can be evenly dispersed in the starch system. Carboxymethyl cellulose is a water-soluble cellulose derivative with good film-forming and dispersibility, which helps to improve the dispersibility and stability of starch and nano-silicon dioxide. The modified starch obtained has good hardness, heat resistance and toughness, and is applied to waste tile sand to improve the mixing of various components in waste tile sand, thereby improving the comprehensive performance of waste tile sand.
[0027] Preferably, the mass ratio of the pretreated starch, nano-silicon dioxide and carboxymethyl cellulose is 1:0.2-0.4:0.08-0.1.
[0028] By adopting the above technical scheme, the mass ratio of pretreated starch, nano-silicon dioxide and carboxymethyl cellulose is further limited within a certain range, and the obtained pretreated starch has good comprehensive performance. The pretreated starch has certain viscosity and toughness, the nano-silicon dioxide has good mechanical properties and durability, and can be loaded in the starch structure. The carboxymethyl cellulose has certain viscosity and dispersibility, so that the starch particles and the nano-silicon dioxide are closely bonded, and the mechanical properties of the modified starch are increased. The subsequent application in concrete increases the strength, toughness and durability of the concrete.
[0029] In the second aspect, the present application also provides a method for preparing fan foundation concrete, comprising the following steps: mixing cement, river sand, gravel, water, modified fiber, slag powder, and polycarboxylic acid water reducer evenly, then adding waste tile sand and fly ash and stirring evenly to obtain fan foundation concrete.
[0030] By adopting the above technical scheme and the above preparation method, the operation is simple and the process time is short, which helps to improve the production efficiency of preparing fan foundation concrete. The obtained fan foundation concrete has good mechanical properties.
[0031] In summary, this application has the following beneficial effects: 1. The modified fiber in this application can absorb a large amount of energy when the concrete is impacted, effectively reduce the effect of concentrated stress, prevent the development of concrete cracks, enhance the concrete's impact resistance, earthquake resistance, erosion resistance, and wear resistance, while improving the impermeability, which is conducive to improving the anti-freeze ability.
[0032] 2. In this application, waste tile sand is used as concrete aggregate. Its larger porosity makes the concrete have good thermal insulation properties, increases the water consumption of the standard consistency of the net slurry, shortens the initial setting time, is beneficial to the hydration of cement, and increases the hydration rate.
[0033] 3. In the present application, fly ash improves the workability of concrete, inhibits water seepage, and the active ingredients in fly ash react with cement hydration products to improve the later strength of concrete. DETAILED DESCRIPTION
[0034] The present application is further described in detail below with reference to the embodiments.
[0035] The raw materials used in the examples and comparative examples can all be obtained commercially.
[0036] Preparation example of modified fiber Preparation Example 1-1 The preparation method of the modified fiber comprises the following steps: (1) dispersing 10 kg of silk in 100 L of 6% by mass sodium hydroxide solution to obtain silk protein solution, washing, drying, extruding granulation, and melt spinning at a spinning temperature of 260° C. to obtain silk fibers, which were sheared to a length of 40 mm; (2) dispersing the modified bamboo scraps in 50 L of deionized water, adding the silk fibers obtained in step (1), stirring at 85° C. for 1.5 h, and drying to obtain a mixture; (3) spraying a water-soluble epoxy resin adhesive onto the surface of the mixture in step (2), and drying to obtain modified fibers.
[0037] The mass ratio of silk fiber, modified bamboo chips and water-soluble epoxy resin adhesive is 1:0.3:0.09.
[0038] The preparation method of modified bamboo chips comprises the following steps: dispersing 9 kg of wood chips in 20 L of 3% potassium hydroxide solution, soaking for 2 hours, washing with water, and then dispersing in 40 L of deionized water, adding 2 kg of marble powder, 0.5 kg of sodium lignin sulfonate and 1 kg of xanthan gum, stirring at a temperature of 80° C. for 2 hours, drying, and grinding to obtain modified bamboo chips (fineness 50 mesh).
[0039] The mass ratio of sawdust, marble powder and xanthan gum is 1:0.6:0.2.
[0040] Preparation Example 1-2 The difference from Preparation Example 1-1 is that in step (2), no modified bamboo chips are added.
[0041] Preparation Example 1-3 The difference from Preparation Example 1-1 is that in step (3), no water-soluble epoxy resin adhesive is added.
[0042] Preparation Example 1-4 The difference from Preparation Example 1-1 is that the mass ratio of silk fiber, modified bamboo chips and water-soluble epoxy resin adhesive is 1:0.5:0.07.
[0043] Preparation Example 1-5 The difference from Preparation Example 1-1 is that the mass ratio of silk fiber, modified bamboo chips and water-soluble epoxy resin adhesive is 1:0.1:0.13.
[0044] Preparation Example 1-6 The difference from Preparation Example 1-1 is that, in the preparation method of modified bamboo chips, no marble powder is added.
[0045] Preparation Example 1-7 The difference from Preparation Example 1-1 is that no xanthan gum is added in the preparation method of the modified bamboo chips.
[0046] Preparation Example 1-8 The difference from Preparation Example 1-1 is that the mass ratio of sawdust, marble powder and xanthan gum is 1:0.8:0.1.
[0047] Preparation Example 1-9 The difference from Preparation Example 1-1 is that the mass ratio of sawdust, marble powder and xanthan gum is 1:0.1:0.5.
[0048] Preparation example of waste tile sand Preparation Example 2-1 The method for preparing waste tile sand comprises the following steps: (1) 30 kg of waste tile sand was crushed to a particle size of less than 2 mm, then dispersed in 60 L of 2 mol / L sodium hydroxide solution, immersed at 80° C. for 2 h, washed with water, then dispersed in 60 L of 1 mol / L dilute hydrochloric acid, immersed at room temperature for 2 h, washed with water, filtered, and dried to obtain pretreated waste tile sand; (2) Disperse the modified starch in 80 L of deionized water, stir evenly, add the pretreated waste tile sand in step (1), continue stirring for 1 h, then add silicon carbide whiskers and 5 kg of erythritol, stir at a temperature of 65 ° C for 3 h, dry, and crush to obtain waste tile sand (particle size 1 mm).
[0049] The mass ratio of waste tile sand, modified starch and silicon carbide whiskers is 1:0.6:0.3.
[0050] The preparation method of modified starch comprises the following steps: dispersing 30 kg corn starch in 60 L deionized water, stirring at 80 DEG C for 35 min, adding 5 L hydrochloric acid and 2 kg silane coupling agent KH550, stirring for 2 h, drying to obtain pretreated starch, dispersing the pretreated starch in 60 L deionized water, adding nano silicon dioxide and carboxymethyl cellulose, stirring at 65 DEG C for 2 h, drying, grinding to obtain modified starch.
[0051] The mass ratio of pretreated starch, nano-silicon dioxide and carboxymethyl cellulose is 1:0.2:0.1.
[0052] Preparation Example 2-2 The difference from Preparation Example 2-1 is that in step (2), no modified starch is added.
[0053] Preparation Example 2-3 The difference from Preparation Example 2-1 is that in step (2), silicon carbide whiskers are not added.
[0054] Preparation Example 2-4 The difference from Preparation Example 2-1 is that the mass ratio of waste tile sand, modified starch and silicon carbide whisker is 1:0.8:0.1.
[0055] Preparation Example 2-5 The difference from Preparation Example 2-1 is that the mass ratio of waste tile sand, modified starch and silicon carbide whisker is 1:0.1:0.6.
[0056] Preparation Example 2-6 The difference from Preparation Example 2-1 is that no nano-silicon dioxide is added in the preparation method of the modified starch.
[0057] Preparation Example 2-7 The difference from Preparation Example 2-1 is that carboxymethyl cellulose is not added in the preparation method of the modified starch.
[0058] Preparation Example 2-8 The difference from Preparation Example 2-1 is that the mass ratio of pretreated starch, nano-silicon dioxide and carboxymethyl cellulose is 1:0.4:0.08.
[0059] Preparation Example 2-9 The difference from Preparation Example 2-1 is that the mass ratio of pretreated starch, nano-silicon dioxide and carboxymethyl cellulose is 1:0.1:0.3. Example
[0060] Example 1 A wind turbine foundation concrete comprises the following raw materials by weight: 200 kg of cement, 40 kg of river sand, 33 kg of crushed stone, 120 kg of water, 22 kg of modified fiber, 30 kg of slag powder, 18 kg of waste tile sand, 10 kg of polycarboxylic acid water reducer, and 30 kg of fly ash.
[0061] The preparation method of the above-mentioned fan foundation concrete includes the following steps: mixing cement, river sand, crushed stone, water, modified fiber, slag powder, and polycarboxylic acid water reducer evenly, and then adding waste tile sand and fly ash and stirring evenly to obtain the fan foundation concrete.
[0062] The modified fiber was prepared by using Preparation Example 1-1; and the waste tile sand was prepared by using Preparation Example 2-1.
[0063] Example 2 A wind turbine foundation concrete, which differs from Example 1 in that, by weight, it includes the following raw materials: 220 kg of cement, 45 kg of river sand, 36 kg of crushed stone, 160 kg of water, 25 kg of modified fiber, 35 kg of slag powder, 20 kg of waste tile sand, 15 kg of polycarboxylic acid water reducer, and 25 kg of fly ash.
[0064] Example 3 A wind turbine foundation concrete, which is different from Example 1 in that the modified fiber is prepared using Preparation Example 1-2.
[0065] Example 4 A wind turbine foundation concrete, which is different from Example 1 in that the modified fiber is prepared using Preparation Examples 1-3.
[0066] Example 5 A wind turbine foundation concrete, which is different from Example 1 in that the modified fiber is prepared using Preparation Examples 1-4.
[0067] Example 6 A wind turbine foundation concrete, which is different from Example 1 in that the modified fiber is prepared using Preparation Examples 1-5.
[0068] Example 7 A wind turbine foundation concrete, which is different from Example 1 in that the modified fiber is prepared using Preparation Examples 1-6.
[0069] Example 8 A wind turbine foundation concrete, which is different from Example 1 in that the modified fiber is prepared using Preparation Examples 1-7.
[0070] Example 9 A wind turbine foundation concrete, which is different from Example 1 in that the modified fiber is prepared using Preparation Examples 1-8.
[0071] Example 10 A wind turbine foundation concrete, which is different from Example 1 in that the modified fiber is prepared using Preparation Examples 1-9.
[0072] Embodiment 11 A wind turbine foundation concrete, which differs from Example 1 in that waste tile sand is prepared using Preparation Example 2-2.
[0073] Example 12 A wind turbine foundation concrete, which differs from Example 1 in that waste tile sand is prepared using Preparation Example 2-3.
[0074] Embodiment 13 A wind turbine foundation concrete, which differs from Example 1 in that waste tile sand is prepared using Preparation Examples 2-4.
[0075] Embodiment 14 A wind turbine foundation concrete, which differs from Example 1 in that waste tile sand is prepared using Preparation Examples 2-5.
[0076] Embodiment 15 A wind turbine foundation concrete, which differs from Example 1 in that waste tile sand is prepared using Preparation Examples 2-6.
[0077] Example 16 A wind turbine foundation concrete, which differs from Example 1 in that waste tile sand is prepared using Preparation Examples 2-7.
[0078] Embodiment 17 A wind turbine foundation concrete, which differs from Example 1 in that waste tile sand is prepared using Preparation Examples 2-8.
[0079] Embodiment 18 A wind turbine foundation concrete, which differs from Example 1 in that waste tile sand is prepared using Preparation Examples 2-9.
[0080] Comparative Example Comparative Example 1 A wind turbine foundation concrete, which differs from Example 1 in that no modified fiber is added.
[0081] Comparative Example 2 A wind turbine foundation concrete, which differs from Example 1 in that the modified fiber is replaced by an equal amount of fiber.
[0082] Comparative Example 3 A wind turbine foundation concrete, which differs from Example 1 in that no waste tile sand is added.
[0083] Performance testing The wind turbine foundation concrete prepared in Examples 1-18 and Comparative Examples 1-3 was subjected to performance tests; The obtained concrete was made into cubic samples of 150mm×150mm×150mm, and the samples were tested in accordance with GB / T50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete".
[0084] The concrete water penetration resistance test is carried out in accordance with GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete".
[0085] After the cubic sample was placed in a standard curing room for 28 days, its compressive strength and flexural strength were measured in accordance with the Standard Test Methods for Mechanical Properties of Ordinary Concrete GB / T50081-2002. The test instrument model was YES-2000 digital display pressure testing machine.
[0086] GB / T50082-2009 “Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete” was used to conduct 28d shrinkage performance test; the test results are shown in Table 1.
[0087] Table 1 Test data of embodiments and comparative examples It can be seen from Table 1 that the wind turbine foundation concrete prepared in Examples 1-2 of the present application has good mechanical properties and mechanical strength, wherein the splitting tensile strength of Example 1 is 7.89 MPa, the maximum water seepage pressure is 2.3 MPa, the compressive strength is 79.8 MPa, the bending strength is 9.8 MPa, and the shrinkage rate is 0.0021%. This shows that the prepared wind turbine foundation concrete has good mechanical properties and mechanical strength, and the various components cooperate with each other to form a high-performance, high-durability concrete structure, ensuring the quality and durability of the concrete.
[0088] In the preparation method of the modified fiber of Examples 3-4, modified bamboo chips and water-soluble epoxy resin adhesive are not added respectively, and the mass ratio of silk fiber, modified bamboo chips and water-soluble epoxy resin adhesive is changed in Examples 5-6. As can be seen from Table 1, the test results of splitting tensile strength, maximum water seepage pressure resistance, compressive strength, flexural strength and shrinkage rate of Examples 3-4 are significantly worse than those of Examples 1-2 and Example 5, while the corresponding performance test of Example 6 is better than that of Examples 3-4, but worse than that of Examples 1 and Example 5, indicating that Silk fibers have high strength, high toughness, good wear resistance and corrosion resistance. Modified bamboo chips have good adsorption, toughness and crack resistance. Modified bamboo chips can be loaded on the surface of silk fibers to improve the mechanical properties of silk fibers. Water-soluble epoxy resin adhesives have excellent bonding properties, wear resistance and corrosion resistance, which allows modified bamboo chips to stably adhere to the surface of silk fibers, increasing the waterproofness and durability of silk fibers, and subsequently improving the compressive, tensile and shear strength of concrete, thereby extending the service life of concrete.
[0089] In the preparation method of modified bamboo chips in Examples 7-8, marble powder and xanthan gum are not added respectively, and the mass ratio of sawdust, marble powder and xanthan gum is changed in Examples 9-10. It can be seen from Table 1 that the test results of splitting tensile strength, maximum water seepage resistance, compressive strength, flexural strength and shrinkage rate of Examples 7-8 are significantly better than those of Example 3, and the corresponding performance test of Example 10 is better than that of Examples 7-8, but worse than that of Example 9, indicating that marble powder can be loaded on the surface and pores of sawdust to improve the strength and durability of sawdust, and xanthan gum has good viscosity and fluidity, so that marble powder adheres to the surface of sawdust, improves the mechanical properties of sawdust, and is subsequently applied to concrete to improve the working performance and durability of concrete.
[0090] In the preparation method of waste tile sand in Examples 11-12, modified starch and silicon carbide whiskers are not added respectively, and the mass ratio of waste tile sand, modified starch and silicon carbide whiskers is changed in Examples 13-14. It can be seen from Table 1 that the test results of splitting tensile strength, maximum water seepage pressure resistance, compressive strength, flexural strength and shrinkage rate of Examples 11-12 are significantly worse than those of Examples 1-2 and Example 13, while the corresponding performance test of Example 14 is better than that of Examples 11-12, but worse than that of Example 1 and Example 13, indicating that waste tile sand has more pores, silicon carbide whiskers have very high strength and modulus, can be loaded on the surface and pores of waste tile sand, improve the tensile strength, flexural strength, toughness and wear resistance of waste tile sand, modified starch makes waste tile sand and silicon carbide whiskers adhere closely, increases the strength and durability of waste tile sand, and is subsequently applied to concrete, so that concrete has better crack resistance and deformation resistance when facing external force, thereby extending the service life of concrete.
[0091] In the preparation methods of the modified starches of Examples 15-16, nano-silicon dioxide and carboxymethyl cellulose are not added respectively. In Examples 17-18, the mass ratio of pretreated starch, nano-silicon dioxide and carboxymethyl cellulose is changed. As can be seen from Table 1, the test results of splitting tensile strength, maximum water seepage pressure resistance, compressive strength, flexural strength and shrinkage rate of Examples 15-16 are significantly better than those of Example 11, while the corresponding performance test of Example 18 is better than that of Examples 15-16, but worse than that of Example 17, indicating that nano-silicon dioxide has good mechanical properties and durability and can be loaded in the starch structure. Carboxymethyl cellulose makes the starch particles and nano-silicon dioxide adhere tightly, thereby increasing the mechanical properties of the modified starch. The subsequent application in concrete increases the strength, toughness and durability of the concrete.
[0092] No modified fiber or waste tile sand is added to Comparative Example 1 and Comparative Example 3, respectively. As can be seen from Table 1, the test results of splitting tensile strength, maximum water pressure resistance, compressive strength, flexural strength and shrinkage rate of Comparative Example 1 and Comparative Example 3 are significantly worse than those of Examples 1-2, indicating that the modified fiber has good toughness and strength, can enhance the impact resistance and wear resistance of concrete, while improving the impermeability and the comprehensive performance of concrete; waste tile sand as concrete aggregate can improve the mechanical strength and wear resistance of concrete and extend the durability of concrete.
[0093] In Comparative Example 2, the modified fiber is replaced by an equal amount of fiber. As can be seen from Table 1, the test results of splitting tensile strength, maximum water seepage pressure resistance, compressive strength, flexural strength, and shrinkage rate of Comparative Example 2 are significantly worse than those of Examples 1-2, but better than those of Comparative Example 1, indicating that the modified fiber of the present application has better mechanical properties, thereby improving the mechanical properties of concrete and maintaining the structural strength and stability of concrete.
[0094] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A wind turbine foundation concrete, characterized in that: The raw materials include, by weight: 200-220 parts of cement, 40-45 parts of river sand, 33-36 parts of crushed stone, 120-160 parts of water, 22-25 parts of modified fiber, 30-35 parts of slag powder, 18-20 parts of waste tile sand, 10-15 parts of polycarboxylic acid water reducer and 25-30 parts of fly ash.
2. A wind turbine foundation concrete according to claim 1, characterized in that: The method for preparing the modified fiber comprises the following steps: (1) dispersing silk in a sodium hydroxide solution to obtain a silk protein solution, washing, drying, extruding granulation, and melt spinning to obtain silk fibers; (2) dispersing the modified bamboo chips in deionized water, adding the silk fibers from step (1), stirring at a temperature of 80-85° C. for 1-2 h, and drying to obtain a mixture; (3) Spraying a water-soluble epoxy resin adhesive onto the surface of the mixture in step (2), and drying the mixture to obtain modified fibers.
3. A wind turbine foundation concrete according to claim 2, characterized in that: The mass ratio of the silk fiber, the modified bamboo scraps and the water-soluble epoxy resin adhesive is 1:0.3-0.5:0.07-0.
09.
4. The wind turbine foundation concrete according to claim 2, characterized in that: The preparation method of the modified bamboo chips comprises the following steps: dispersing the wood chips in a potassium hydroxide solution, soaking for 1-2 hours, washing with water, and then dispersing in deionized water, adding marble powder, sodium lignin sulfonate and xanthan gum, stirring at a temperature of 75-80°C for 1-2 hours, drying, and grinding to obtain the modified bamboo chips.
5. The wind turbine foundation concrete according to claim 4, characterized in that: The mass ratio of the sawdust, marble powder and xanthan gum is 1:0.6-0.8:0.1-0.
2.
6. The wind turbine foundation concrete according to claim 1, characterized in that: The method for preparing waste tile sand comprises the following steps: (1) crushing the waste tile sand to a particle size of less than 2 mm, then dispersing it in a sodium hydroxide solution, soaking it at 75-80° C. for 1-2 hours, washing it with water, and then dispersing it in dilute hydrochloric acid, soaking it at room temperature for 1-2 hours, washing it with water, filtering it, and drying it to obtain pretreated waste tile sand; (2) Dispersing the modified starch in deionized water, stirring evenly, adding the pretreated waste tile sand in step (1), continuing to stir, then adding silicon carbide whiskers and erythritol, stirring at a temperature of 60-65° C. for 2-3 hours, drying, and crushing to obtain waste tile sand.
7. The wind turbine foundation concrete according to claim 6, characterized in that: The mass ratio of the waste tile sand, the modified starch and the silicon carbide whisker is 1:0.6-0.8:0.1-0.
3.
8. The wind turbine foundation concrete according to claim 6, characterized in that: The preparation method of the modified starch comprises the following steps: dispersing corn starch in deionized water, stirring at a temperature of 76-80°C for 30-35 minutes, adding hydrochloric acid and a silane coupling agent, stirring for 1-2 hours, and drying to obtain pretreated starch; dispersing the pretreated starch in deionized water, adding nano silicon dioxide and carboxymethyl cellulose, stirring at a temperature of 60-65°C for 1-2 hours, drying, and grinding to obtain modified starch.
9. The wind turbine foundation concrete according to claim 7, characterized in that: The mass ratio of the pretreated starch, nano silicon dioxide and carboxymethyl cellulose is 1:0.2-0.4:0.08-0.
1.
10. The method for preparing wind turbine foundation concrete according to claim 1, characterized in that: The method comprises the following steps: mixing cement, river sand, crushed stone, water, modified fiber, slag powder and polycarboxylic acid water reducing agent evenly, then adding waste tile sand and fly ash and stirring evenly to obtain fan foundation concrete.
Citation Information
Cited By
Fiber-reinforced high-performance geopolymer concrete and preparation method thereof
CN122355629A